Pengaruh Literasi Keuangan Terhadap Perilaku Manajemen Keuangan Melalui Gaya Hidup Hedonisme Sebagai Variabel Intervening - Harningsih, Sri; Rachma, N.; Ramadhan, Tri Sugiarti (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This study aims to analyze the effect of financial literacy on financial management behavior through hedonistic lifestyle as an intervening variable among economics faculty students. This research uses quantitative methods with Smart Partial Least Square (SmartPLS) path analysis techniques. The respondents of this study were 110 economics faculty students selected by purposive sampling technique. Data was collected using a questionnaire consisting of three variables, namely financial literacy, financial management behavior, and hedonistic lifestyle. Data were analyzed using SmartPLS 3.0. The results of this study indicate that: (1) Financial literacy has a significant positive effect on financial management behavior directly, (2) Financial literacy has a significant positive effect on hedonistic lifestyle directly, (3) Hedonistic lifestyle has an insignificant negative effect on financial management behavior, (4) Hedonistic lifestyle is not proven to mediate the effect of financial literacy on financial management behavior. The higher the financial literacy, the better the financial management behavior, regardless of the influence of hedonistic lifestyle. The implication of this research is the need to improve financial literacy without having to consider the influence of hedonistic lifestyle on financial management behavior.. Keywords: Financial Literacy, Financial Management Behavior, Hedonistic Lifestyle